The agrarian, structural and cultural constraints of smallholders’ readiness for sustainability standards implementation: The case of Indonesian Sustainable Palm Oil in East Kalimantan - Dharmawan, A.H.; Mardiyaningsih, D.I.; Rahmadian, F.; Yulian, B.E.; Komarudin, Heru; Pacheco, P.; Ghazoul, J.; Amalia, R. (MDPI, 2021)
The expansion of oil palm plantation has caused adverse impacts on the ecosystem. It has been associated with deforestation, biodiversity loss, disturbances to environmental services and livelihood change. The government of Indonesia has made an effort to control the negative effects by issuing relevant policies. One of the policies is Indonesian Sustainable Palm Oil (ISPO)’s sustainability standards to which large-scale plantations and smallholders are obliged to adhere. This study assesses the readiness of two types of smallholders, namely, the nucleus–plasma scheme and independent smallholders to adopt ISPO standards. Using a case study research approach in two oil palm plantation villages in East Kalimantan, the study found out a number of ISPO implementation challenges, grouped into structural and socio-cultural challenges, which make smallholders less ready to adhere to this mandatory policy. Coping with these challenges, this study proposed that land and business legality programs be expedited to strengthen property rights, and that training and education programs be intensified to enhance awareness, knowledge and capacity of smallholders to enable them to comply with sustainability standards.